Deletion of Dock10 in B Cells Results in Normal Development but a Mild Deficiency upon In Vivo and In Vitro Stimulations - Gerasimčik, Natalija; He, Minghui; Baptista, Marisa A. P.; Severinson, Eva; Westerberg, Lisa S. (Frontiers in Immunology, 2017)
We sought to identify genes necessary to induce cytoskeletal change in B cells. Using gene expression microarray, we compared B cells stimulated with Interleukin-4 (IL-4) and anti-CD40 antibodies that induce B cell spreading, cell motility, tight aggregates, and extensive microvilli with B cells stimulated with lipopolysaccharide that lack these cytoskeletal changes. We identified 84 genes with 10-fold or greater expression in anti-CD40+IL-4 stimulated B cells, one of these encoded the guanidine nucleotide exchange factor (GEF) dedicator of cytokinesis 10 (Dock10). IL-4 selectively induced Dock10 expression in B cells. Using lacZ expression to monitor Dock10 promoter activity, we found that Dock10 was expressed at all stages during B cell development. However, specific deletion of Dock10 in B cells was associated with a mild phenotype with normal B cell development and normal B cell spreading, polarization, motility, chemotaxis, aggregation, and Ig class switching. Dock10 deficient B cells showed lower proliferation in response to anti-CD40 and IL-4 stimulation. Moreover, the IgG response to soluble antigen in vivo was lower when Dock10 was specifically deleted in B cells. Together, we found that most B cell responses were intact in the absence of Dock10. However, specific deletion of Dock10 in B cells was associated with a mild reduction in B cell activation in vitro and in vivo.